Microphysiological system design: simplicity is elegance. (March 2020) - Hinman, Samuel S.; Kim, Raehyun; Wang, Yuli; Phillips, K. Scott; Attayek, Peter J.; Allbritton, Nancy L.
Abstract: Design parameters for microphysiological systems (MPSs) are driven by the need for new tools to answer questions focusing on human physiology in a robust and reliable manner. Within this perspective, engineering benchmarks and principles are identified to guide the construction of new devices in the MPS field, with emphasis placed on the design principles common to all tissues and those unique to a subset of tissues. Leading organ replica technologies that recapitulate various functions of the brain, heart, intestine, and lung are highlighted as examples that meet the identified benchmarks and standards, with current barriers for large-scale production and commercialization discussed. To reach their full potential and achieve widespread use, MPSs will have to be recognized officially by government agencies, and toward this end, considerations of the MPS as a potential regulatory tool are presented.